PENGARUH PERBEDAAN KETINGGIAN TEMPAT TERHADAP KUALITAS FISIK DAN KIMIA JAMBU BIJI (PSIDIUM GUAJAVA L.) KULTIVAR GETAS MERAH - Wahyuni, Siti; Budirokhman , Dodi; Zidni Ilman, Nida Rezkia (Agroswagati : Jurnal Agronomi, 2024)
This study aims to determine the effect of altitude differences on the physical and chemical quality of guava fruit (Psidium guajava L.), Getas Merah cultivar. The research was conducted in September 2023 at the Laboratory of the Faculty of Agriculture, Universitas Swadaya Gunung Jati, Cirebon, using an experimental method with a Completely Randomized Design (CRD) consisting of three treatments (highland, midland, and lowland) and nine replications. Observed parameters included fresh weight, weight loss, fruit firmness, total soluble solids, vitamin C content, and organoleptic tests. The results showed that altitude significantly affected all observed parameters. Guavas from low and mid-altitudes showed better quality in terms of weight loss, total soluble solids, and organoleptic attributes, while guavas from high altitudes had higher initial weight, firmness, and vitamin C content. These differences were influenced by variations in temperature, humidity, rainfall, and harvest time across locations. It is recommended to choose planting locations based on desired fruit quality: low and mid-altitudes for better taste and appearance, and high altitudes for better texture and nutritional content. Further research using different guava cultivars is suggested to obtain broader insights.